2022
DOI: 10.1177/00033197221135950
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein to Albumin Ratio as a Predictor of Contrast-Induced Nephropathy After Carotid Angiography

Abstract: This study evaluated the role of the C-reactive protein (CRP)/albumin ratio (CAR) in estimating the probability of occurring contrast-induced nephropathy (CIN) after carotid artery angiography (CAAG). Patients (n = 410) who had CAAG for carotid artery stenosis (CAS) were included in this study. A spike in serum creatinine was used to define CIN within 72 h of the procedure (>.5 mg/dL or >25% above baseline). CAR was calculated by dividing the CRP by the albumin level. Patients with CIN had higher numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…In addition, the capacity of these indices to predict CIN was not limited to patients undergoing PCI. Previous studies have reported that CRP or SII levels were exhibited significant diagnostic performance (32,33). However, the CANLPH score was found to be a better predictor with stronger diagnostic performance compared to the SII.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the capacity of these indices to predict CIN was not limited to patients undergoing PCI. Previous studies have reported that CRP or SII levels were exhibited significant diagnostic performance (32,33). However, the CANLPH score was found to be a better predictor with stronger diagnostic performance compared to the SII.…”
Section: Discussionmentioning
confidence: 72%